1993
DOI: 10.1073/pnas.90.3.853
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in C3H/10T1/2 mouse embryonic cells: evidence for internucleosomal DNA modification in the absence of double-strand cleavage.

Abstract: Apoptosis in embryonic C3H/10T/2 (done 8) cells is marked by specific changes in morphology and DNA fragmentation that differ from those found in apoptotic thymocytes. These results demonstrate that ultrastructural changes within the nucleus associated with endonucleolytic degradation are linked with structural degradation at higher levels of chromatin organization. Strand modifications within the internucdeosomal linker region are shown to involve alkaline-sensitive sites that appear to be sensitive to Si end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0
1

Year Published

1994
1994
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(72 citation statements)
references
References 13 publications
4
67
0
1
Order By: Relevance
“…The existence of ss breaks in apoptotic DNA fragments has been clearly demonstrated (Figure 1). 7,51,52 The rate of nuclear proteolysis might also be a factor determining the extent of DNA fragmentation, since rapid protein degradation and collapse of nuclear structure might stop DNA cleavage at any given stage. This would explain the fact that DNA degradation never proceeds to completion and that the DNA ladder is not always observed even in cells containing nucleases capable of internucleosomal DNA cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of ss breaks in apoptotic DNA fragments has been clearly demonstrated (Figure 1). 7,51,52 The rate of nuclear proteolysis might also be a factor determining the extent of DNA fragmentation, since rapid protein degradation and collapse of nuclear structure might stop DNA cleavage at any given stage. This would explain the fact that DNA degradation never proceeds to completion and that the DNA ladder is not always observed even in cells containing nucleases capable of internucleosomal DNA cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA within domains is more protected by virtue of its interaction with core histones and histone H1. Evidence that the internucleosomal linker region becomes somehow modified, increasing its nuclease sensitivity, prior to cleavage was provided by Tomei et al (1993) who showed that the larger fragments of DNA from apoptotic C3H/10T cells (which do not normally degrade their DNA to small fragments) appeared to contain a modification in the linker region that was sensitive to alkali and to S1 nuclease. In another study, Pietsch et al (1993) analyzed the small oligonucleosomal fragments generated at the completion of DNA degradation in apoptotic thymocytes and showed that numerous singlestrand breaks (ssb) were present in the linker regions.…”
Section: Introductionmentioning
confidence: 99%
“…These DNA ladders are derived from large fragments of DNA of 30-50 and 200-300 kbp, which may in terms of higher-order chromatin structure represent loops and rosettes of DNA [10][11][12]. Internucleosomal cleavage of DNA now appears to be a relatively late event in the apoptotic process, which in some models may be dissociated from early critical steps [13,14]. Nevertheless, its measurement is simple and it is often used as a major criterion to determine whether a cell is apoptotic.…”
Section: Introductionmentioning
confidence: 99%